Natural Climate Solutions must embrace multiple perspectives to ensure synergy with sustainable development - Waring, Bonnie G.; Gurgel, Angelo; Köberle, Alexandre C.; Paltsev, Sergey; Rogelj, Joeri (Frontiers in Climate, 2023)
To limit global warming to well below 2°C, immediate emissions reductions must be coupled with active removal of greenhouse gases from the atmosphere.'Natural Climate Solutions' (NCS) achieve atmospheric CO2 reduction through the conservation, restoration, or altered management of natural ecosystems, 1,2 with enormous potential to deliver 'win-win-win' outcomes for climate, nature and society.Yet the supply of high-quality NCS projects does not meet market demand, and projects already underway often fail to deliver their promised benefits, due to a complex set of interacting ecological, social, and financial constraints. How can these cross-sectoral challenges be surmounted? Here we draw from expert elicitation surveys and workshops with professionals across the ecological, sociological, and economic sciences, evaluating differing perspectives on NCS, and suggesting how these might be integrated to address urgent environmental challenges. We demonstrate that funders' perceptions of operational, political, and regulatory risk strongly shape the kinds of NCS projects that are implemented, and the locations where they occur. Because of this, greenhouse gas removal through NCS may fall far short of technical potential.Moreover, socioecological co-benefits of NCS are unlikely to be realized unless the local communities engaged with these projects are granted ownership over implementation and outcomes.